Knowledge, awareness and practice study for mosquito borne diseases among school children of Malwa region of India - Taran, Shachi Jain; Taran, Rakesh; Bhandari, Virendra (Indian Journal of Child Health, 2016)
Background: Mosquito borne diseases pose significant burden to the community which can be prevented through right knowledge, attitude and practice of it. Objective: To study the knowledge, awareness and practices of school children about mosquito borne diseases. Materials and Methods: A predesigned, semi structured proforma was filled out from 261 students of 9th to 12th standard of Malwa region. Data was entered in Microsoft excel and percentage of answers were calculated. Results: All students knew something about the mosquito borne diseases. Most of the students (>80%) knew about the malaria and dengue. Very few students were having knowledge that Japanese encephalitis, yellow fever and filariasis are spread though mosquito. 68.2% of students knew fever with chills as symptoms of mosquito borne diseases. More than 85% of students told that mosquito borne diseases can be prevented either through individual protection or through community level protection, supported by government. Conclusion: The awareness regarding malaria was good among students of Malwa region but same was lacking about other mosquito borne diseases.